ANALYSING THE INFLUENCE OF TECHNOLOGICAL PARAMETERS ON THE PROCESS OF LASER MARKING OF SURFACE OF ANODISED ALUMINIUM SAMPLES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The requirements for marking in terms of contrast and durability are constantly increasing. In order to meet all these challenges, it is necessary to carry out research leading to the optimisation and increase in efficiency of the technological process of laser marking. In the case of aluminium, the contrast and durability of the marking depend on the values of the laser marking parameters. In order to determine the optimal laser marking method, experimental studies have been carried out, controlling the power, speed, frequency, pulse duration and line raster step for a specific anodised aluminium. The studies carried out were analysed and subsequently optimized to obtain a contrast marking. A Rofin PowerLine F 20 Varia fiber laser system and aluminium alloy 1050 with anodised surface were used for the research. The surface changes after the laser treatment were analysed using a laser scanning microscope and contrast determination method. The dependence of contrast and roughness on speed, power, frequency and raster step was analysed. Comparative plots of contrast and roughness variations versus laser marking technological parameters were constructed.